2014
DOI: 10.1146/annurev-physiol-030212-183735
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticles, Lung Injury, and the Role of Oxidant Stress

Abstract: The emergence of engineered nanoscale materials has provided significant advancements in electronic, biomedical, and material science applications. Both engineered nanoparticles and nanoparticles derived from combustion or incidental processes exhibit a range of physical and chemical properties, which have been shown to induce inflammation and oxidative stress in biologic systems. Oxidative stress reflects the imbalance between the generation of reaction oxygen species (ROS) and the biochemical mechanisms to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
66
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(68 citation statements)
references
References 127 publications
2
66
0
Order By: Relevance
“…This indicated that particle exposure could induce a transient production of ROS after 3 h, but an adaptive response to oxidative stress could be induced after a longer exposure period. Our result is also in keeping with a current hypothesis describing a hierarchical tiered oxidative stress response that minor oxidative stress induces defense mechanisms; whereas higher levels initiate specific signaling pathways that lead to injury and cytotoxicity (Madl et al, 2014).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This indicated that particle exposure could induce a transient production of ROS after 3 h, but an adaptive response to oxidative stress could be induced after a longer exposure period. Our result is also in keeping with a current hypothesis describing a hierarchical tiered oxidative stress response that minor oxidative stress induces defense mechanisms; whereas higher levels initiate specific signaling pathways that lead to injury and cytotoxicity (Madl et al, 2014).…”
Section: Discussionsupporting
confidence: 91%
“…4). Other studies have shown that exposure to PM induced oxidative stress, which generally is considered to play an important role in PM induced toxicity Madl et al, 2014) and adverse vascular effects (Araujo and Nel, 2009;Donaldson et al, 2013;Miller et al, 2012;Shrey et al, 2011). Previous work also showed that exposure to 100 g/ml, but not lower concentrations of DEP SRM 2975, significantly induced ROS in THP-1 macrophages (Jantzen et al, 2012).…”
Section: Discussionmentioning
confidence: 94%
“…In addition to their potential impact on the environment and public health, nanoparticles play important roles in diverse fields of applications. Example applications of nanoparticles have been reviewed from various perspectives [1][2][3][4][5]. Properties of nanoparticles are strongly dependent on their physical sizes.…”
Section: Introductionmentioning
confidence: 99%
“…The neurotrophins, a family of closely related proteins, were initially identified as survival factors for sensory and sympathetic neurons. 40 Neurotrophins are also related to survival, development, and functioning of neurons in both the peripheral and the central nervous systems. 40 Disruption of cellular 41 This effect might be associated with the balance in the biological levels of zinc ions.…”
mentioning
confidence: 99%
“…40 Neurotrophins are also related to survival, development, and functioning of neurons in both the peripheral and the central nervous systems. 40 Disruption of cellular 41 This effect might be associated with the balance in the biological levels of zinc ions. Glutathione metabolism and metabolism of xenobiotics by cytochrome P450 are important pathways in regulation of oxidative stress in cells.…”
mentioning
confidence: 99%